IMPLEMENTASI METODE TARTILA DALAM MENINGKATKAN KOMPETENSI MEMBACA AL-QUR`AN PARA SANTRI DI TPQ AL-HIDAYAH DESA KARANG PRANTI PAJARAKAN PROBOLINGGO - Susanti, Mutiara; Hifdil Islam, Muhammad; Inzah, M. (Jurnal Bilqolam Pendidikan Islam, 2025)
This study aims to describe the implementation and evaluation of the Tartila method in improving the Qur'anic reading competence of students at TPQ Al-Hidayah, Karang Pranti Village, Pajarakan, Probolinggo. This research employs a qualitative approach in the form of a case study. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that the Tartila method is implemented systematically through stages such as letter recognition, sorogan learning (individual recitation), intensive guidance, and three types of evaluation: daily evaluation, level advancement evaluation, and graduation assessment including the final ceremony. This method significantly enhances students’ ability to read the Qur'an, particularly in terms of fluency, accuracy in pronouncing hijaiyah letters, and mastery of tajwid rules. The personalized and evaluative learning approach enables effective and continuous Qur'anic education. The successful implementation of the Tartila method is also supported by the active role of caregivers and dedicated ustadz or ustadzah who patiently and consistently guide the students.